Frekuensi Aktivitas Fisik terhadap Tingkat Indeks Masa Tubuh Pada Mahasiswa Universitas Pendidikan Indonesia - Putri, Dewi Arras; Damayanti, Welsi; Rasyid, Diva Khadijah (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
The purpose of this study is to analyze the relationship between the frequency of physical activity and Body Mass Index (BMI) among students at the Universitas Pendidikan Indonesia. The method employed in this research is a qualitative approach, where data is presented descriptively through the collection of information using questionnaires distributed to students. The results indicate that students with low levels of physical activity have a higher proportion in the underweight and obesity categories, while those who are physically active show better BMI status. These findings highlight the importance of physical activity in maintaining health and preventing obesity. Therefore, efforts are needed to raise awareness among students regarding the significance of exercising and healthy eating habits to achieve an ideal BMI.